2021
DOI: 10.3390/ijerph182312296
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chemical Sensitivity in Patients Exposed to Moisture Damage at Work and in General Working-Age Population—The SAMDAW Study

Abstract: A considerable proportion of patients having respiratory tract or voice symptoms associated with workplace moisture damage (MD) could have multiple chemical sensitivity (MCS). MCS is characterized by symptoms of different organ systems in association with low-level chemical exposure. The objective of this study was to assess the prevalence of MCS among patients referred to secondary health care because of respiratory or voice symptoms associated with workplace MD compared to the general working-age population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Earlier in comparison with the general population, MCS was found common in this patient group [ 35 ]. In this study when comparing with asymptomatic controls, this finding was confirmed.…”
Section: Discussionmentioning
confidence: 78%
“…Earlier in comparison with the general population, MCS was found common in this patient group [ 35 ]. In this study when comparing with asymptomatic controls, this finding was confirmed.…”
Section: Discussionmentioning
confidence: 78%